Workshop an alternative way of learning for Medical Graduates - Balaji Arumugam; Saranya Nagalingam (International Journal of Medical Research and Review, 2015)
Background: Workshops with group discussions play a valuable role in the all-round education of students. Discussion in workshops develops the more instrumental skills of listening, presenting ideas, persuading and working as a part of a team.Objectives: The purpose of this study was to assess the outcome of a research workshop conducted among medical students.Materials and Methods: The concept of learning and improvement in knowledge was evaluated among various medical college students belonging different semesters attending a research workshop using pre and post test questionnaire method. The workshop was divided into six groups with scientific sessions of 40 minutes followed by group activities.Results: The workshop had greatly improved the knowledge among the participants with mean knowledge scoring of 3.49 before to 9.76 after the workshop and female medical students showed more improvement in knowledge scoring than males which was statistically significant.Conclusion: Our study had explored that the workshop with group activities could be used as a powerful tool in medical education for improvement of knowledge among medical students.